Examination of Self-Confidence and Metacognition Levels of High School Students Case of Karabuk Province - Aslan, Huseyin; Sahin, Musa (Asian Journal of Education and Training, 2020)
The aim of the study is to determine the relationship between self-confidence and metacognition of high school students and to contribute to the development of students. The study conducted in accordance with this purpose is correlational research. 420 students from different high schools participated in the study. 48.1% (202) of the students are female and 51.9% (218) are male. It consists of 7 different high schools where the students participated in the study and studied in the province of Karabük. The research findings were expressed as n, (%), mean and standard deviation, and were considered significant at p <0.05 significance level. All statistical calculations were made in SPSS 22.0 V. statistics package program. Considering all the findings and related researches obtained, it is seen that metacognitive skill plays an important role in students’ success. In addition to this, it was observed that the success levels of students who developed the metacognitive strategy increased. In modeling, teachers can draw the attention of students to this area by presenting slices from their own lives and enable them to learn their skills in this area. Based on this, education that will improve students’ metacognitive skills should be provided in all educational processes.